Critical Reflections on Time and Capitalism - Thomas Klikauer (tripleC: Communication, Capitalism & Critique)
Abstract: Wayne Hope’s book on Time, Communication and Global Capitalism highlights how capitalism depends on two central issues: communication and time.  In that, Hope’s analysis goes well beyond the famous quote on time by the comedian Dave Allen “we spend our lives on the run: we get up by the clock, eat and sleep by the clock, get up again, go to work - and then we retire. And what do they [fucking] give us? A clock”. Hope emphasises the conflicts between two key time concepts: a) real-time and b) clock time. But the books also discusses ideas such as presentism, temporality, coevalness and allochronism. All these notions affect how capitalism communicates time to us. The book, rather convincingly, argues that all these versions of time are part of global media capitalism, financial regimes and the political economies in general. As a consequence, they also shape today’s workplaces and everyday life.